Thirty-Day Unplanned Readmission After Ambulatory Laparoscopic Cholecystectomy in Western China: A Retrospective Study - MingJun, Huang (Cureus, 2021)
Background Day surgery has been gradually accepted by health professions globally, which can shorten the hospital stay and reduce medical costs. The ambulatory laparoscopic cholecystectomy (LC) has been performed in China since over 10 years. However, few studies focus on its 30-day unplanned readmission rate of ambulatory LC and no standard of unplanned readmission rate for that now. Purpose This study aimed to evaluate the unplanned readmission rate and the reasons readmission after ambulatory LC in a tertiary hospital, which is the earliest ambulatory surgery implementation place in western China. Methods A retrospective analysis was conducted. The patients who underwent ambulatory LC from September 2015 to September 2019 in West China Hospital were screened. The 30-day unplanned readmission rate was calculated as the first outcome. The reasons for unplanned readmission were analyzed and classified as the second outcome. Results The study included 3,014 patients, and the unplanned readmission rate was 1.53%. The rate of patients diagnosed with cholecystolithiasis with cholecystitis was significantly higher in the unplanned readmission group (73.9% vs. 48.9%, p=0.003), and medical cost of unplanned readmission patients was significantly more than that of non-readmission patients (8,102.4±1,375.7 Yuan vs. 7,574.61±10,14.0 Yuan; p=0.008). It was observed that 71.7% readmission happened in the first seven days. Wound problems (60.9%) and abdominal pain (26.1%) went the two main reasons for unplanned readmission. Conclusions The analysis revealed that the unplanned readmission rate of 1.53% was low for ambulatory LC. Some causes of unplanned readmission, such as abdominal pain and wound site pain, wound exudate could be reduced by some simple interventions of the clinical professions.